2011
DOI: 10.1002/uog.9092
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal micronized progesterone and risk of preterm delivery in high‐risk twin pregnancies: secondary analysis of a placebo‐controlled randomized trial and meta‐analysis

Abstract: Objectives Progesterone treatment reduces the risk of preterm delivery in high-risk singleton pregnancies. Our aim was to evaluate the preventive effect of vaginal progesterone in high-risk twins.Methods This was a subanalysis of a Danish-Austrian, double-blind, placebo-controlled, randomized trial (PREDICT study)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 28 publications
0
46
0
5
Order By: Relevance
“…To date, progesterone has not been shown to be beneficial in unselected twin pregnancies 16 -19 . Data on twins with cervical shortening are limited to secondary analyses of randomized controlled trials 20,21 . These studies failed to show a benefit of progesterone but lack sufficient power.…”
Section: Discussionmentioning
confidence: 99%
“…To date, progesterone has not been shown to be beneficial in unselected twin pregnancies 16 -19 . Data on twins with cervical shortening are limited to secondary analyses of randomized controlled trials 20,21 . These studies failed to show a benefit of progesterone but lack sufficient power.…”
Section: Discussionmentioning
confidence: 99%
“…29 Nevertheless, it is difficult to draw conclusions because the number of women with twin pregnancies analysed in all of these studies was relatively small and the definition of a short cervix was not uniform. 5,15,28,29 In our trial, we had a very low incidence of women with a previous preterm delivery and/or a short cervix ( Table 1).…”
Section: Vaginal Progesterone In Twin Pregnanciesmentioning
confidence: 92%
“…Although it has been suggested that the mechanisms underlying the parturition process in twins may differ from those in singletons, 28 this has not yet been proven. The different sensitivities to progestogen supplementation depending on the risk factors also suggest that there may be more than one pathway leading to spontaneous preterm labour.…”
Section: Vaginal Progesterone In Twin Pregnanciesmentioning
confidence: 98%
See 1 more Smart Citation
“…Subanalysen der anderen Studien zur Prävention der Frühgeburt durch die Gabe von Progesteron konnten dies bestä-tigen [40,48,49,50,51] …”
Section: Progesteron Und Mehrlingsgraviditätunclassified